Antioxidant supplementation slows telomere shortening in free-living white stork chicks. Issue 1918 (15th January 2020) - Pineda-Pampliega, Javier; Herrera-Dueñas, Amparo; Mulder, Ellis; Aguirre, José I.; Höfle, Ursula; Verhulst, Simon
Abstract : Telomere length (TL) and shortening is increasingly shown to predict variation in survival and lifespan, raising the question of what causes variation in these traits. Oxidative stress is well known to accelerate telomere attrition in vitro, but its importance in vivo is largely hypothetical. We tested this hypothesis experimentally by supplementing white stork ( Ciconia ciconia ) chicks with antioxidants. Individuals received either a control treatment, or a supply of tocopherol (vitamin E) and selenium, which both have antioxidant properties. The antioxidant treatment increased the concentration of tocopherol for up to two weeks after treatment but did not affect growth. Using the telomere restriction fragment technique, we evaluated erythrocyte TL and its dynamics. Telomeres shortened significantly over the 21 days between the baseline and final sample, independent of sex, mass, size and hatching order. The antioxidant treatment significantly mitigated shortening rate of average TL (−31% in shorter telomeres; percentiles 10th, 20th and 30th). Thus, our results support the hypothesis that oxidative stress shortens telomeres in vivo .